Three Cases of Recurrent Hepatocellular Carcinoma with Bone Metastasis Appearing with Particular Symptomes - Yamamoto, Masayuki; Yoshioka, Masakazu; Sugahara, Katsuhiko; Iizuka, Hidehiko; Miura, Kazuo; Kohno, Tetsuo (Nippon Shokaki Geka Gakkai zasshi, 1990)
Recurrence of three hepatocellular carcinomas after primary liver resection was discovered in the bones by particular symptoms relating to their location. Case 1: a 58-year-old male, 2 years and 6 months after the operation, had sensory disturbance below C4, paraplegy and vesicorectal disturbance, and signs of transection. MR imaging showed a metastatic lesion at the 4th cervical vertebra and a shirt of the spinal cord to the right. We diagnosed the condition as cervical vertebral metastasis of the hepatocellular carcinoma. Case 2: A 53-year-old male, 6 months after the operation, had sudden severe left chest pain and dyspnea. He received hemothorax and a computed tomogram showed a large mass protruding from the left 3rd rib in the left chest cavity. The pleural bleeding was diagnosed as being caused by rupture of the metastatic region at the rib. TAE was effective in stopping the bleeding. Case 3: A 61-year-old male, 6 months after the operation, had uncontrolled nasal bleeding. Biopsy revealed metastasis of hepatocellular carcinoma to the nasal bone and nasal mucosa. Ligation of the right external carotid artery was not able to stop the bleeding.